The world upside down: the first Kefersteinia (Orchidaceae: Zygopetalinae) with non-resupinate flowers - Carnevali, Germán; Cetzal-Ix, William; Tapia-Muñoz, José L.; Romero-González, Gustavo A. (Phytotaxa, 2015)
A new species of Kefersteinia (Orchidaceae, Zygopetalinae), K. carolorum, from the state of Táchira, Venezuela, is herein described, illustrated, and characterized based on morphological features. Kefersteinia carolorum is similar to K. lactea from Costa Rica, but it differs in the non-resupinate flowers and the longer callus. The labellum in the upper-most position that distinguishes this species is unique in the genus but has evolved independently in Zygopetalinae at least three times. Evolutionary, ecological, and functional implications of this character are explored. The conservation status of the new taxon is assessed as DD according to IUCN (International Union for Conservation of Nature) criteria. We also provide a key to identify the genera of the Zygopetalinae with labellum in an upper-most position. In addition, we offer a key for the Kefersteinia species from Venezuela, a figure, and a map showing their geographical distributions.